Management of a Difficult-to-Treat Diabetic Foot Wound Complicated by Osteomyelitis: A Case Study - Maram Alkhatieb; Hatan Mortada; Hattan Aljaaly (Case Reports in Surgery)
Introduction. Diabetic ulcers are a major health issue worldwide, causing significant economic burdens and affecting both the patient and the society as a whole. Predisposing factors in diabetic patients, known as the pathogenic triad, comprise trauma, ischemia, and neuropathy. Regardless of the cause, correct diagnosis and prompt treatment are essential in the management of leg ulcers. Case History. We report a case of a 51-year-old male patient, with a known history of type 2 diabetes mellitus who presented to our hospital with a history of two ulcers, one that he was mainly complaining of, which was actively infected and located at the posterior part of the distal left leg, and the second, dry ulcer caused by unrecognized trauma, located on the heel of the same limb. Magnetic resonance imaging showed osteomyelitis and degenerative changes in the calcaneonavicular and tarsal joints. The patient underwent multiple sessions of excisional debridement. He was started on negative pressure wound therapy with some improvements. However, after skin graft failure, Nanoflex powder was used, leading to complete wound closure within one month of treatment. Conclusion. A multidisciplinary holistic approach must be used when treating diabetic foot ulcers. Different modalities and sessions of debridement should be performed after optimizing the general condition of the patient.